1980
DOI: 10.1007/bf00540132
|View full text |Cite
|
Sign up to set email alerts
|

Fire, fungi, and beetle influences on a lodgepole pine ecosystem of south-central Oregon

Abstract: Interactions between fire, fungi, bark beetles and lodgepole pines growing on the pumice plateau of central Oregon are described. Mountain pine beetle (Dendroctonus ponderosae) outbreaks occur mainly in forests that are 80-150 years old with a mean diameter of about 25 cm and weakened by a fungus, Phaeolus schweinitzii. The outbreak subsides after most of the large diameter trees are killed. The dead trees fuel subsequent fires which return nutrients to the soil, and a new age class begins. The surviving fire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 7 publications
0
49
1
Order By: Relevance
“…Geiszler et al (1980) and Gara et al (1985) concluded that fire-damaged lodgepole pine are more prone to certain fungal infections, and that these trees are more susceptible to mountain pine beetle infestation. Schowalter et al (1981) hypothesized a similar situation with the southern pine beetle in the coniferous forests of the southeast.…”
Section: The }mentioning
confidence: 99%
See 1 more Smart Citation
“…Geiszler et al (1980) and Gara et al (1985) concluded that fire-damaged lodgepole pine are more prone to certain fungal infections, and that these trees are more susceptible to mountain pine beetle infestation. Schowalter et al (1981) hypothesized a similar situation with the southern pine beetle in the coniferous forests of the southeast.…”
Section: The }mentioning
confidence: 99%
“…5. An illustration of the fungus/bark beetle/fire interaction proposed by Geiszler et al (1980) and Gara et al (1985). …”
Section: The }mentioning
confidence: 99%
“…are killed more frequently than smaller ones (Hopping and Beall 1948). Potential reasons for this pattern are that large trees may be preferentially attacked (Shepherd 1966;Geiszler et al 1980;Mitchell and Preisler 1991;Preisler 1993), provide a larger landing surface (Hynum and Berryman 1980), or have a larger basal area (Safranyik et al 1975;Burnell 1977;Coulson 1979). Large diameter trees usually have thick phloem providing high beetle reproduction potential (Amman 1969(Amman , 1972Katovich and Lavigne 1986;and Shrimpton and Thomson (1985) for specific situations when this is not the case).…”
Section: Introductionmentioning
confidence: 99%
“…Swetnam and Betancourt 1992;Veblen et al 1999Veblen et al , 2000Heyerdahl et al 2002) or examined interactions among forest processes without incorporating climate variation (e.g. Geiszler et al 1980;Hadley and Veblen 1993;Veblen et al 1994). Other work has attempted to incorporate climate variation, fire, and insect outbreaks, but has yielded generally qualitative results or had difficulty sep- (Gedalof and Smith 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Knight 1987;Anderson et al 1987;Hadley 1994), confounding our understanding of climate-disturbance relationships (e.g. Speer et al 2001;Dale et al 2001) and little previous research has examined the interrelationships of more than two of these processes (but see Geiszler et al 1980;Veblen et al 1994;Kramer et al 2001).…”
Section: Introductionmentioning
confidence: 99%